Infographic visualization - Tey, Xue Yi (2018)
Basic charts and tables are important when illustrating data, they enable users to easily visualise data, making it easier for them read and analyse data. This effectively guides users to a concluding statement. Compared with basic charts and tables, info graphic visualization is a tool that is able to display and analyse data in a more creative and simplified way for users to comprehend all the complex information with the aid of graphics. It also allows users to make comparisons with the given information. Thus, it allows information to be read, understood and absorbed easily. The differences between the basic charts and tables versus infographic visualization is that info graphic visualization includes the analyzing of data which allows users to identify the data, trend and the issue that is raised in the visualization almost instantaneously when looking at it while the basic charts and tables requires users to self-deduce the trend of data and the issue. This objective of this project is to be able to use infographic visualization to display a group of students' results in the perspective of the course instructor as well as individual student. This project aims to be able to be effectively applied across the TEL system such that it will allow educators to keep track of their students’ learning progress with ease and for the student to better keep track of their learning journey. Thus far, this project is able to show the results of 100 students over a period of 12 weeks from both the instructor’s and student’s perspective. It provides an analysis of the data set and allows the user to identify key issues such as mean, top and bottom percentile instantaneously. This project proves that it is more efficient than the basic charts and tables currently being used to present the student’s results. With the increase in size of the student pool, the system can instantaneously highlight the performance of the class as well the students that will require more attention and help from the educators. As such, this would reduce the time required for the standard process of inserting results, computing the mean and highlighting the bottom percentile that the educators have to spend on every test.